The Development of E-Comic Learning Media for Elementary School Mathematics Learning - Vera Fahreza; Juliana M. Sumilat; Dini Anggraheni; Cinta Wayansari; Leonard Leonard (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
This research aims to produce a mathematics learning media in e-comics for one year of learning in grade 2 elementary school. This research refers to the 4-D Development Model consisting of 4 steps, namely: (1) define, (2) design, (3) develop, and (4) disseminate. The validation test results from 2 material experts showed an average percentage of 94% and 97%, while the validation test of 2 media experts showed an average percentage of 97% and 92%. Based on these data, the E-Comic Learning Media is decent to use.